2015
DOI: 10.5539/hes.v6n1p53
|View full text |Cite
|
Sign up to set email alerts
|

To Speak Like a TED Speaker—A Case Study of TED Motivated English Public Speaking Study in EFL Teaching

Abstract: This paper intends to investigate the effectiveness of a new course pattern-TED-motivated English Public Speaking Course in EFL teaching in China. This class framework adopts TED videos as the learning materials to stimulate students to be a better speaker. Meanwhile, it aims to examine to what extent the five aspects of language skills are improved. Participants are required to give answers to the questions in the questionnaires. SPSS 15.0 is used to analyze the data. The result shows that students in this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…Ted is a private, non-profit organization founded for spreading valuable ideas (Broadaway, 2012). It has become the most popular venue for sharing innovative and engaging topics that have exceeded its original three fields of Technology, Entertainment, and Design (Broadaway, 2012;Hashimoto, Fukuda, & Okazaki, 2015;Li et al, 2016). Ted website is a valuable teaching tool.…”
Section: 4youtube and Ted Talksmentioning
confidence: 99%
See 1 more Smart Citation
“…Ted is a private, non-profit organization founded for spreading valuable ideas (Broadaway, 2012). It has become the most popular venue for sharing innovative and engaging topics that have exceeded its original three fields of Technology, Entertainment, and Design (Broadaway, 2012;Hashimoto, Fukuda, & Okazaki, 2015;Li et al, 2016). Ted website is a valuable teaching tool.…”
Section: 4youtube and Ted Talksmentioning
confidence: 99%
“…Listening to Ted Talks also activates and promotes students' critical analysis. They listen critically in order to distinguish between facts and opinions, judge the validity of the evidences, analyze the whole content and decide to what extent they agree with the speaker (Li et al, 2016). Based on their scaffolding efficiency, further studies are recommended to investigate the effect of Ted Talk videos on students' achievements other than the listening and public speaking skills (Li et al, 2016).…”
Section: 4youtube and Ted Talksmentioning
confidence: 99%
“…Ketam suggested that from watching the videos, students "can improve [their] pronunciation and how to get the audience attention also". Similar to Li et al (2016), TED videos showed positive impact on gestural abilities. Some students such as Yvette and Cindy expressed that the videos offered them models of physical actions and postures to emulate.…”
Section: Evidence Of Scaffolded Learning With Mediation Videosmentioning
confidence: 69%
“…For the research, models of good presentations were also provided to encourage students to closely study reputable models (Hayward 2017) such as observing TED (Technology, Entertainment, and Design) presenters (Li, Gao & Zhang 2016). These models provided students with structured input that demonstrates how to support their content more convincingly and attract audience attention (Leopold 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Videos have proved to be meaningful items for students' learning. Li, Gao, and Zhang (2016) suggest that "students do not only retell what they have heard from the video, but also integrate their own idea to create their own speech" (p. 56). From this perspective, students are able to become creative language users since they start to incorporate features from the videos into their conversations and interactions.…”
Section: Video-mediated Listeningmentioning
confidence: 99%